2005
DOI: 10.1029/2005gl024083
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic pulsations caused by the Sumatra earthquake on December 26, 2004

Abstract: A long period Pc5 pulsation was observed at Phimai in Thailand, shortly after the origin time of the Sumatra earthquake on December 26, 2004. The localized nature and the period of oscillations suggest that the long period magnetic pulsation was generated by dynamo action in the lower ionosphere, set up by an atmospheric pressure pulse which propagated vertically as an acoustic wave when the ocean floor suddenly moved vertically. It is speculated that a Pc3 type pulsation observed at Tong Hai in China, 10 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 10 publications
6
94
1
3
Order By: Relevance
“…Iyemori et al (2005) describe a pulsation of period 3.6 min (Pc5) observed in Phimai, Thailand, 12 min after the Sumatra earthquake on 26…”
Section: Geomagnetic Pulsationsmentioning
confidence: 99%
“…Iyemori et al (2005) describe a pulsation of period 3.6 min (Pc5) observed in Phimai, Thailand, 12 min after the Sumatra earthquake on 26…”
Section: Geomagnetic Pulsationsmentioning
confidence: 99%
“…First, co-/post-seismic phenomena have been reported. Iyemori et al (2005) reported geomagnetic pulsations that may have been caused by the 2004 S. Hirooka et al: Neural network based tomographic approach Sumatra-Andaman earthquake. The observed geomagnetic pulsations suggest the existence of a large current in space caused by acoustic waves based on surface displacements.…”
Section: Introductionmentioning
confidence: 99%
“…3). In addition to seismic waves detected by global seismic networks (Park et al, 2005); co-seismic displacement measured by GPS (Vigny et al, 2005); oceanic sea surface variations measured by altimetry (Smith et al, 2005); detection of magnetic anomaly (Balasis & Mandea, 2007;Iyemori et al, 2005) and acoustic-gravity waves (Le Pichon et al, 2005); a series of ionospheric disturbances, observed with different techniques, have been reported in the literature (DasGupta et al, 2006;Liu et al, 2006a;Lognonné et al, 2006;Occhipinti et al, 2006;2008b). Two ionospheric anomalies in the plasma velocities were detected North of the epicenter by a Doppler sounding network in Taiwan (Liu et al, 2006a).…”
Section: The Modern Debatementioning
confidence: 99%